2012
DOI: 10.1152/ajpregu.00330.2011
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal cortex endocannabinoid system modulates baroreflex activity through CB1receptors

Abstract: [481][482][483][484][485][486][487][488] 2006) have shown that glutamatergic synapses in the ventral portion of the medial prefrontal cortex (vMPFC) modulate baroreflex activity. Moreover, glutamatergic neurotransmission in the vMPFC can be modulated by the endocannabinoids system (eCBs), particularly the endocannabinoid anandamide, through presynaptic CB 1 receptor activation. Therefore, in the present study, we investigated eCBs receptors that are present in the vMPFC, and more specifically whether CB1 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…CB1 receptors are located presynaptically in glutamatergic neuron terminations within the vMPFC (Devane et al, 1988), where they can modulate glutamate release (Auclair et al, 2000). Moreover, recent work from our group has shown that activation of vMPFC CB1 receptors decreases both cardiac baroreflex bradycardic and tachycardic responses (Ferreira-Junior et al, 2012), i.e., an effect opposite to that observed with stimulation of the glutamatergic system (Resstel and Correa, 2006c), which suggests that the vMPFC endocannabinoid system can influence baroreflex activity probably by modulating glutamate release. However, the role of vMPFC NMDA receptors in the cardiac sympathetic component of the baroreflex was not investigated.…”
mentioning
confidence: 88%
“…CB1 receptors are located presynaptically in glutamatergic neuron terminations within the vMPFC (Devane et al, 1988), where they can modulate glutamate release (Auclair et al, 2000). Moreover, recent work from our group has shown that activation of vMPFC CB1 receptors decreases both cardiac baroreflex bradycardic and tachycardic responses (Ferreira-Junior et al, 2012), i.e., an effect opposite to that observed with stimulation of the glutamatergic system (Resstel and Correa, 2006c), which suggests that the vMPFC endocannabinoid system can influence baroreflex activity probably by modulating glutamate release. However, the role of vMPFC NMDA receptors in the cardiac sympathetic component of the baroreflex was not investigated.…”
mentioning
confidence: 88%
“…Moreover, some studies have already demonstrated that Ang II blunts the arterial baroreflex sensitivity[14, 17]. The arterial baroreflex sensitivity is usually evaluated by reflex changes of heart rate in response to changes in arterial blood pressure, namely the arterial baroreflex control of heart rate[18, 19]. To further explore the mechanisms about blunted arterial baroreflex sensitivity in the CHF state, the first aim in this study was to test whether the regulatory effect of Ang II on the aortic baroreceptor neurons contributes to the deficiency in the arterial baroreflex control of heart rate in CHF.…”
Section: Introductionmentioning
confidence: 99%
“…The MPFC is a region that sends projections to brainstem areas related to cardiovascular tonic control (Fisk & Wyss, 2000;Vertes, 2004). Furthermore, the MPFC modulates baroreflex function (Ferreira-Junior et al 2012, 2013. Therefore, the MPFC may be a part of the neural circuitry that allows the VH to modulate cardiac baroreflex function.…”
Section: Discussionmentioning
confidence: 99%
“…Linear regression was generated matching induced mean arterial pressure (MAP) variations with reflex HR responses. Paired values of MAP ( MAP) and HR ( HR) variations were plotted to create the linear regression for each rat, and their slopes were compared to test changes in baroreflex gain (Ferreira-Junior et al 2012). We have used linear regression to analyse either bradycardia or tachycardia responses separately (Alves et al 2009a).…”
Section: Methods Of Baroreflex Evaluationmentioning
confidence: 99%
See 1 more Smart Citation